Implementation of problem-based learning in a typical engineering classroom - Abd. Hamid, Mohd. Kamaruddin; Abu Hassan, Mohd. Ariffin; Hassim, Mimi Haryani; Mohd. Yusof, Khairiyah (2004)
Problem-based learning (PBL) approaches to engineering education often generate justifiable enthusiasm among faculty who has become frustrated with the limitations of traditional lecture-based education. However, faculty contemplating a change to a problem-based format rarely anticipates the many practical difficulties that can destroy one's enthusiasm and create chaos in the classroom. This paper describes in detail the implementation of PBL, a teaching method that incorporates realistic experiences in the classroom. This implementation technique has been used for two semesters in an undergraduate Chemical Engineering class in the Faculty of Chemical and Natural Resources Engineering, Universiti Teknologi Malaysia